Enhancing Students' Soft Skills Through Rohis Extracurricular Activities at MAN Pematang Siantar - Sriwahyuni, Sriwahyuni; Budianti, Yusnaili (FKIP - Universitas Riau, 2025)
This study investigates the effectiveness of Rohis (Islamic Spiritual) extracurricular activities at MAN Pematang Siantar in strengthening students’ soft skills and explores the challenges faced in the process. Using a qualitative descriptive method, data were collected through observation, interviews with mentors, teachers, and active students, as well as documentation of activities and program reports. The findings indicate that Rohis plays a significant role in developing communication, leadership, teamwork, and responsibility through programs such as public speaking training, trilingual study sessions, Qur’an recitation, calligraphy, and religious outreach. School support is provided through mentor guidance and basic facilities; however, challenges persist, including limited time due to a dense curriculum, inadequate facilities, low membership in certain branches, varying skill levels among students, lack of awareness and commitment, and insufficient technical training for the Rohis committee. Therefore, it is concluded that future development should be strategically planned by enhancing committee training, creating more flexible activity schedules, and securing stronger institutional support so that Rohis can continue contributing meaningfully to students’ character formation and soft skill improvement.